The Agony House - Priest, Cherie; OConnor, Tara (New York, New York : Arthur A. Levine Books, an imprint of Scholastic Inc., 2018)
Seventeen-year-old Denise Farber, her mom, and her stepfather are moving back to New Orleans, into the Argonne house, which is over 100 years old, and really showing its age, but which her mother plans to turn into a bed-and-breakfast. But old houses have histories, and sometimes ghosts, and a mysterious old comic book that Denise finds in the attic may hold the answer to a crime and the terrifying things that keep happening in what she thinks of as the "Agony" house.
"This book contains 45 interior comic illustrations in addition to the text"--Provided by publisher.
HL740
Accelerated Reader
Keywords: Ghost stories; Haunted houses; Juvenile fiction; Murder; Juvenile fiction; Comic books, strips, etc; Haunted houses -- Fiction; Murder -- Fiction; Ghosts; Fiction; Haunted houses -- Fiction; Murder -- Fiction; Cartoons and comics; New Orleans (La.); Juvenile fiction; New Orleans (La.) -- Fiction; New Orleans (La.) -- Fiction